The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1095/biolreprod.104.031302
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Impact on Cross-Genus Cloned Fish Derived from Transgenic Common Carp (Cyprinus carpio) Nuclei and Goldfish (Carassius auratus) Enucleated Eggs1

Abstract: In previous studies of nuclear transplantation, most cloned animals were obtained by intraspecies nuclear transfer and are phenotypically identical to their nuclear donors; furthermore, there was no further report on successful fish cloning since the report of cloned zebrafish. Here we report the production of seven cross-genus cloned fish by transferring nuclei from transgenic common carp into enucleated eggs of goldfish. Nuclear genomes of the cloned fish were exclusively derived from the nuclear donor speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 33 publications
1
76
0
1
Order By: Relevance
“…Since the technique of plasmid rescue was firstly described by Perucho et al [13]), it has been utilized in the study of transgenic mice [14][15][16][17], transgenic tomato [18] and transgenic Drosophila [19], but it has rarely, to our knowledge, been employed previously in the study of transgenic fish. Recently, we briefly reported three integration-site sequences in F4 transgenic fish [20]; however, the detailed integration pattern of transgene in F4 transgenic fish needs to be clarified. Here we adopted the method of plasmid rescue to study the copy number, manner and sites of transgene integration in the F4 pMThGH-transgenic fish.…”
Section: Introductionmentioning
confidence: 99%
“…Since the technique of plasmid rescue was firstly described by Perucho et al [13]), it has been utilized in the study of transgenic mice [14][15][16][17], transgenic tomato [18] and transgenic Drosophila [19], but it has rarely, to our knowledge, been employed previously in the study of transgenic fish. Recently, we briefly reported three integration-site sequences in F4 transgenic fish [20]; however, the detailed integration pattern of transgene in F4 transgenic fish needs to be clarified. Here we adopted the method of plasmid rescue to study the copy number, manner and sites of transgene integration in the F4 pMThGH-transgenic fish.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cross-genus cloned fish derived from common carp nuclei and goldfish enucleated eggs was given birth [11]. The result showed that the somitogenesis progress and vertebral numbers of the cloned fish were consistent to the egg-providing species, but not to the donor cell species.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, substantial efforts have been undertaken to understand the interaction between nucleus and cytoplasm in fish, with the majority of studies performed using NT embryos [6,[18][19][20][21]. In the present study, a relatively innovative system anchored on crossbred embryos of zebrafish and Chinese rare minnow was utilized to address this question, since RZ embryos could be safely considered as the cross-species NT embryos derived from ZR nuclei and Chinese rare minnow egg cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not the case for cross-species NT, wherein enucleated eggs cytoplasm had an obvious impact on the mitochondrial genetic materials and the development of NT embryos [6,7]. www.theriojournal.com Available online at www.sciencedirect.com Theriogenology 70 (2008) [1525][1526][1527][1528][1529][1530][1531][1532][1533][1534][1535] Our previous study revealed that the somitogenesis and vertebral number of the cross-genus cloned fish resembled those of the cytoplasmic recipient species, goldfish, instead of the donor nuclear species, common carp [6]. Therefore, the crosstalk between the donor nucleus and the recipient egg cytoplasm from different species could modify the early development of NT embryo, possibly by affecting gene expression of the transplanted nucleus.…”
Section: Introductionmentioning
confidence: 99%